Modulation of the intermolecular interaction of myoglobin by removal of the heme. (1st October 2013) - Imamura, Hiroshi; Morita, Takeshi; Sumi, Tomonari; Isogai, Yasuhiro; Kato, Minoru; Nishikawa, Keiko
<x xml:space="preserve">Abstract</x> Toward understanding intermolecular interactions governing self‐association of proteins, the present study investigated a model protein, myoglobin, using a small‐angle X‐ray scattering technique. It has been known that removal of the heme makes myoglobin aggregation‐prone. The interparticle interferences of the holomyoglobin and the apomyoglobin were compared in terms of the structure factor. Analysis of the structure factor using a model potential of Derjaguin–Laudau–Verwey–Overbeek (DLVO) suggests that the intermolecular interaction potential of apomyoglobin is more attractive than that of holomyoglobin at short range from the protein molecule.